Enzyme nanoparticles : preparation, characterisation, properties and applications - Pundir, Chandra S. (Micro & nano technologies., 2015)
This book is the first book in English on nanotechnology and nanomaterials integrating with enzymatic systems, with a focus on nanoparticles and biological applications. It covers comprehensively the relevant topics to understand the development of enzyme nanoparticles as it relates to the complicated structures of enzyme nanoparticles and their functionalization and immobilization on to various supports. The preparation of enzyme nanoparticles, their kinetic properties and applications after immobilization of the immobilized enzyme nanoparticles is described. The use of colour images in all formats of the book will improve the understanding of the topics covered. The book offers an integration of Enzymology and Nanotechnology and provides the latest information on preparation of enzyme nanoparticles, their characterization, their functionalization and immobilization on to various supports and thereafter their kinetic properties and applications in various industries with special reference to Biosensor Technology.